Weighted Best Local Approximation (Analysis in Theory and Applications, 2016)
In this survey, the notion of a balanced best multipoint local approximation is fully exposed since they were treated in the $L^p$ spaces and recent results in Orlicz spaces. The notion of balanced point, which was introduced by Chui et al. in 1984 is extensively used.
Keywords: Best local approximation; multipoint approximation; balanced neighborhood.